By the Grace of God: Women’s Agency in the Rhetoric of Katharina Schütz Zell and Martin Luther - Mikkola, Sini Karoliina (Vox Scripturae - Revista Teológica Internacional, 2025)
The present article employs a micro-historical analysis of the interaction between Katharina Schütz Zell and Martin Luther in the 1520s to examine the women’s agency in the context of the Protestant Reformation. Schütz Zell, a devout laywoman residing in Strasbourg, defiantly challenged prevailing social and ecclesiastical norms by publicly advocating for clerical marriage and defending her own union with Pastor Matthias Zell. It has been posited that Schütz Zell employed strategies of theological and rhetorical legitimation to substantiate her public actions, anchoring her position on divine grace and biblical antecedents. Concurrently, Luther endorsed her work with great enthusiasm, despite the fact that her theoretical writings upheld the gender hierarchy. The apparent contradiction between the normative principles of theology and the pastoral practices observed in the sixteenth century underscores the intricacies of women’s agency within the socio-cultural milieu of that era. As demonstrated by the findings of the research, Schütz Zell belongs to a more extensive tradition of women who, between the 14th and 16th centuries, asserted their right to public expression in the name of the Christian faith. To summarise, it can be posited that, despite being regarded as an anomaly by her contemporaries, Schütz Zell represents a significant conduit in the history of women’s agency during Europe’s religious transformations.